A randomized clinical trial of class II composite restorations using direct and semidirect techniques - Torres, Carlos Rocha Gomes [UNESP]; Mailart, Mariane Cintra [UNESP]; Crastechini, Érica [UNESP]; Feitosa, Fernanda Alves [UNESP]; Esteves, Stella Renato Machado [UNESP]; Di Nicoló, Rebeca [UNESP]; Borges, Alessandra Bühler [UNESP] (Springer Nature, 2019)
Objective: This prospective study evaluated the clinical performance of large class II restorations made with different techniques over 24 months. Materials and methods: Thirty patients received two class II restorations (n = 60) using a nanohybrid composite and different restorative techniques (direct (DT), semidirect (SDT)), in a split-mouth randomized design. The same adhesive system was applied for all restorations. For DT, the restorative material was applied directly inside the tooth preparation. For SDT, a tooth preparation impression was obtained using alginate and a silicone flexible die was prepared. The restoration was made chairside on the model and additionally light cured. After that, it was cemented in preparation using resinous cement. All restorations were evaluated using the FDI criteria after 7 days, 6, 12, and 24 months postoperatively. Results: After 24 months, 24 patients attended the recall and 48 restorations were evaluated. Fisher’s statistical analysis (5%) showed no difference between the techniques. Nevertheless, Friedman’s test showed significant differences for some criteria after 12 months of evaluation for both techniques. Postoperative sensitivity was reported in one DT restoration. Also, after 24 months, one SDT restoration presented marginal fracture, which was deemed unsatisfactory. Conclusions: After a 24-month follow-up, no significant difference between the tested techniques was detected. The restorations performed with both techniques produced clinically acceptable restorations. Clinical relevance: This study demonstrated the viability of applying two different operatory techniques (direct and semidirect) for class II resin composite restorations.
Keywords: Composites; Dental clinics; Randomized controlled clinical trials; Restorative dentistry: operative